Peran Environmental Identity Terhadap Sikap Pariwisata Berkelanjutan Pada Masyarakat Desa Tuk-Tuk, Samosir, Sumatera Utara - Nikki Lauda; Christiawan Christiawan; Nathalie Fransisca; Claresta Kangginata; Rianda Elvinawanty (Magister Tourism Study, Faculty of Tourism, Udayana University, 2022)
This study aims to determine the existence of an environmental identity relationship to sustainable tourism attitudes in communities living in Tuk-Tuk Village, Samosir, North Sumatra. The hypothesis in this study is that there is a positive relationship between environmental identity and sustainable tourism attitudes in the people who live in Tuk-Tuk Village, Samosir, North Sumatra. The research subjects used in this study were 301 residents of Tuk-Tuk Siadong Village, Simanindo, Samosir. The sampling technique used was purposive sampling method. This research uses quantitative methods, research data is collected using a scale. The assumption test used consists of a normality test anda linearity test. Data were analyzed using Pearson Product Moment correlation test with the help of SPSS 20 for Windows. The results of the data analysis show that there is a positive relationship between environmental identity and the attitude of sustainable tourism in the people who live in Tuk-Tuk Village, Samosir, North Sumatra. Keywords: Environmental Identity, Samosir, Sustainable Tourism.